ANALYSIS OF MONETARY INDICATOR VARIABLES ON THE STABILITY OF PRICES OF GOODS AND SERVICES BEFORE AND DURING THE COVID- 19 PANDEMIC - Gulo, Antonius; Bakhtiar Efendi; Wahyu Indah Sari (PT. Arsil Reka Engineering, 2023)
This study aims to analyze the contributions of the variable interactions of monetary policy in the stability ofgoods and services prices. Where is the monetary policy variable (inflation, kurs, consumer price index, grossdomestic products, the money supply, and interest rates). Research in conducted in the country of Indonesia and uses secondary data or time series from 2008 to 2021. The data analysis model in this study is Simultaneous Model and Different Test. Simultaneous equations to analyze the relation between independent and variable variables found in the research country. Whereas different tests examine the different monetary policy variables before and during the covid-19 pandemic. Simultaneous analysis of equations on statistical test common equation 1 suggests that variable interest rates, money distribution, exchange rates and consumerprice indexes have significant adverse effects on the INF. Whereas in the same equation 2, it suggests that gross domestic product variables have a positive relationship that is significant to the CPI. And inflation has a negative relationship significantly insignificant t CPI. And different test results show that inflation movement, kurs, money supply, interest rates and CPI before and during the covid-19 pandemic in Indonesia indicate significant results. For this reason, the researcher hopes that the monetary authority, namely Bank Indonesia, can improve monetary stability and maintain the BI rate in regulating the money supply so that it can suppressthe inflation rate as an effort to stabilize the prices of goods and services.